The Subject’s Embodiment In The Midst of Ontology And Ethics: A Phenomenological Survey of The Body In Martin Heidegger And Emmanuel Levinas’ Thoughts - Mohammadreza Rikhtegaran; Alireza Sayadmansour (Pizhūhish/hā-yi Falsafī- Kalāmī, 2019)
Received: 01/02/2018       |       Accepted: 09/04/2019 In his Being and Time, Heidegger does not illustrate Dasein’s embodiment but he postpones his illustration for some time in the future, namely in his Zollikon Seminars (1959-1969). In the seminars, Heidegger provides his clearest elucidation for this primordial fact that Dasein’s embodiment is openness to the world; Dasein’s existence extends beyond and over its physical body thereby construing and analysing the world from an existential standpoint. He puts forward the title “bodying forth” for this primordial fact. Dissimilarly, Levinas, by adopting his peculiar ethical approach, criticises the Heideggerian Dasein: Heideggerian Dasein is sufficiently not human (i.e. “from flesh-and-blood”). Levinas lays stress upon the fact that the subject’s face-to-face encounter with the Other can be taken from the perspective of embodied reality. A novel wisdom of the body will be constituted in the context of the I’s ethical relationship with the Other and the I’s widely open receptivity to fulfilling the Other’s demands and needs. In this paper, having made an investigation into the subject’s embodiment in both philosophers’ different phenomenologies, a serious scrutiny will be given to the Levinasian critique of Dasein as it is insufficiently constituted “from flesh-and-blood 🞕 Rikhtegaran, M., & Sayadmansour, A. (2019). The Subject’s Embodiment In The Midst of Ontology And Ethics: A Phenomenological Survey of The Body In Martin Heidegger And Emmanuel Levinas’ Thoughts. The Journal of Philosophical - Theological Research, 21(79), 71۔96. https://doi.org/10.22091/jptr-pfk.2019.2889.1825